TANAH DAN KEWARGANEGARAAN: PROPOSAL DALAM MEMAHAMI DISKRIMINASI RUANG HIDUP DAN IDENTITAS WARGA TIONGHOA - Luthfi, Ahmad Nashih Luthfi Nashih (Lensa Budaya: Jurnal Ilmiah Ilmu-Ilmu Budaya, 2019)
This article contains a proposal to understand violence mainly the one practiced by the state towards the Chinese communities in Indonesia. This perspective looks at the interweaving of the practices of violence between discrimination based on one?s identity and ideology with the seizure and denial of rights to land and properties. These practices of violence which caused the exclusion of Indonesian citizens of Chinese descents in Indonesia were conducted through law and regulations, through the expression of power through brute force, and through continuous questioning the legitimation of their citizenship status, all were used to legitimate their discrimination which later made such discrimination socially and politically acceptable. This series of interconnected discrimination can be traced back all the way to colonial era, independence era, post-1965 which gave rise to Soeharto to power, even until today. Specifically, this article elaborates on the seizure of properties owned by Chinese communities in post-1965 and the ownership and control of these properties in various areas in Indonesia until today.  Keywords: citizenship, Chinese, perampasan property, post-1965